Efforts To Improve the Motor Development of Children with Down Syndrome: Narrative Review - Risna Junianti; Endang Susilowati; Arum Meiranny (LPPM Universitas Harapan Bangsa, 2025)
Background: In children with Down syndrome, the patterns of gross and fine motor development follow the same patterns as in normal children, but developmental milestones are achieved at a later time. There are several reasons why children with Down syndrome experience delayed motor development, including cognitive factors, hypotonia, reduced muscle strength, loose joints and ligaments, and hand structure factors. Objective: To determine effective interventions in improving the development of children with Down syndrome. Research Method: Narrative review. Research Results: A review of 15 articles found that the use of trampolines, virtual reality, treadmill exercises, isokinetics, vibration, surfing, traditional Indian dance, computer-based phonics, vestibular stimulation, improvement of numerical skills, the use of picture card media, traditional games such as jamuran and engklek, and sensory integration with busy books can improve the development of children with Down syndrome. Conclusion: There are effects and benefits from the provision of each intervention in various countries on improving the development of children with Down syndrome.